Step & turn—A novel bimodal behavioral biometric-based user verification scheme for physical access control. Issue 118 (July 2022) - Gupta, Sandeep; Kacimi, Mouna; Crispo, Bruno
Abstract: Step & Turn is a novel bimodal behavioral biometric-based verification scheme for physical access control. In today's rapidly evolving smart physical spaces, frictionless and smooth interactions are emerging as critical usability requirements. Such demands need to coexist with mandatory requirements like security. Step & Turn addresses the fundamental limitations of the conventional physical access control schemes, i.e., users having a specific knowledge or possessing a particular device or token, to satisfy both usability and security requirements. We design and develop a prototype of Step & Turn by exploiting two natural human behaviors: single footstep and hand-movement to authenticate the users. To evaluate Step & Turn, we design multi-class verification models using three different classifiers. The system achieves a True Acceptance Rate of 97.25% at False Acceptance Rate of 0.01% on a dataset of 1, 600 samples collected from 40 participants. We also assess its usability using the System Usability Scale. The solution obtained a score of ≈ 76.72 providing evidence that users have a positive perspective towards the use of Step & Turn .